Клинический опыт применения автоматизированного инъектора последнего поколения в амбулаторной стоматологической практике (Эндодонтия Today)
Local anesthesiology in dentistry exist more than 120 years. Nowadays we use it in any time when treatment interfaced with pain. On a boundary of centuries in dental anesthesiology appears a new way connected with development and introduction into daily practice, including endodontic treatment. The usage of automated syringes start this way.